2015
DOI: 10.1590/0103-8478cr20120715
|View full text |Cite
|
Sign up to set email alerts
|

Blackberry (Rubus spp.): influence of ripening and processing on levels of phenolic compounds and antioxidant activity of the 'Brazos' and 'Tupy' varieties grown in Brazil

Abstract: RESUMO Algumas frutas de clima temperado e tropical, principalmente as do tipo "berries", têm como característica o acúmulo de compostos antioxidantes e são objeto de inúmeros estudos, haja vista a sua correlação com os benefícios para a saúde humana. Os objetivos deste trabalho foram quantificar as antocianinas, os compostos fenólicos e mensurar a capacidade antioxidante (ferric reducing antioxidant power -FRAP) de amoraspretas de duas cultivares ('Brazos' e 'Tupy'), nos três estágios de maturação, considerad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 22 publications
2
5
1
Order By: Relevance
“…The phenolic content found in the extract was 5902.89 ± 7.42 mg GAE/L (the phenolic extract had an equivalent of 3300 g of pulp/L). This amount is equal to 177.26 mg GAE/100 g of pulp which falls within the range found for other fruits from the Rubus generum (Zielinski et al, 2015;Ferreira et al, 2010). Rufino et al (2010) suggested a classification scheme where the phenolic content of fruits could be grouped as low if the concentration was <100 mg GAE/100 g of fruit, medium for the range 100-500 mg GAE/100 g and high for >500 mg GAE/100 g. Based on this classification, R. rosaefolius would be classified as having a medium content of phenolic compounds.…”
Section: Phenolic Compositionsupporting
confidence: 80%
“…The phenolic content found in the extract was 5902.89 ± 7.42 mg GAE/L (the phenolic extract had an equivalent of 3300 g of pulp/L). This amount is equal to 177.26 mg GAE/100 g of pulp which falls within the range found for other fruits from the Rubus generum (Zielinski et al, 2015;Ferreira et al, 2010). Rufino et al (2010) suggested a classification scheme where the phenolic content of fruits could be grouped as low if the concentration was <100 mg GAE/100 g of fruit, medium for the range 100-500 mg GAE/100 g and high for >500 mg GAE/100 g. Based on this classification, R. rosaefolius would be classified as having a medium content of phenolic compounds.…”
Section: Phenolic Compositionsupporting
confidence: 80%
“…Kafkas et al [13] ) and sucrose content (2.6, 1.5, 1.4, 1.2 and 2.0 mg g ¡1 ) in Navaho, Chester Thornless, Jumbo, Bursa 2 and Loch Ness blackberry cultivars, respectively, grown in the Mediterranean region of Turkey. The glucose and fructose contents of the wild blackberry accession studied in this research were markedly richer compared to the amounts described by Zielinski et al [19] in Brazos and Tupy blackberries grown in southern Brazil: glucose (3.11 and 3.30 g¢100 g ¡1 ) and fructose (2.86 and 2.49 g¢100 g ¡1 ). Sensoy et al [27] quantified the fructose (8.84À16.31 g kg ¡1 ) and glucose (1.48À3.89 g kg ¡1 ) contents in wild blackberries from Van, Turkey.…”
Section: Sugars Vitamin C and Antioxidant Activitycontrasting
confidence: 61%
“…Blackberry (Rubus fruticosus) is a perennial shrub that is native to Europe (Radovanovi c, Anđelkovi c, Radovanovi c, & Anđelkovi c, 2013) and is characterized by being labor-intensive and also for providing a high economic return (Zielinski et al, 2015). In Mexico, 152,921.52 tons were harvested in 2014, making it the largest producer in North America (SIAP-SAGARPA, 2016).…”
Section: Introductionmentioning
confidence: 99%